Letter (copy) - Wild, Sam
1952 035-0027-005 2. By protesting to the Spanish Embassy, 24, Belgrave Square, London, S.W.1., demanding the immediate release of Lopez Raimundo and his companions and a halt to the persecution of Spanish trade unionists and democrats. 3. By protesting to the Foreign Office against the Government's decision to permit the export of arms and munitions of war to fascist Spain. Should you wish to hear more about the struggle of the Spanish people against Franco's dictatorship, we shall be very pleased to send a speaker to your organisation. Yours fraternally, SAM WILD (President). ALAN GILCHRIST (Vice-President). ALEC DIGGES (Secretary). CPB. EC. 4.12.52. 292/946/35/28(iii)